Specialized nursing professional. Does this specialist make the best use of technology in care? - Rocío Suárez Rodríguez; Jorge Leodan Cabrera Olvera; Irene Mercedes Zapata Silva (Universidad de Ciencias Médicas de La Habana, 2022)
Introduction: The perception of the integrality of care is achieved when the nursing professional integrates, at a high level, the scientific, social, and ethical competencies and the use of technological tools to preserve and recover health, tailored to the needs and expectations of the being cared for. Objective: To analyze the development of scientific evidence on how the specialized nursing professional makes use of technology in the process of caring for the person. Material and Methods: A bibliographic search was carried out in the Scielo, Lilacs, Medline, Redalyc, Scopus, and Google Scholar databases in Spanish, English, and Portuguese. The information was consulted during the 2019-2020 period; a total of 25 references were used for its development. Results: The specialized nursing professional uses technological resources in the care process and other pillars of the work practice that contribute to providing comprehensive care to human beings. Conclusions: The specialized nursing professional makes two major uses of technological resources in the care process: during patient care itself to restore and maintain health, preserving interaction with the family; and in the great pillars of professional practice: management of treatment processes and continuity of care, teaching that ensures the excellence of future professionals, and research, thus approaching the offer of humanized care which is the moral ideal of the profession.